A sensibilidade das plantas de girassol (Helianthus annuus L.) à radiação UV-B é alterada pelo suprimento de nitrogênio - Cechin, Inês [UNESP]; Gonzalez, Gisely Cristina [UNESP]; Corniani, Natália [UNESP]; Fumis, Terezinha de Fátima [UNESP] (FapUNIFESP (SciELO), 2018)
Interaction effects between nitrogen and UV-B radiation were studied in sunflower (Helianthus annuus L. variety IAC-Iarama) plants grown in a greenhouse under natural photoperiod conditions. Plants were irradiated with 0.8W m-2 (control) or 8.0W m-2 (+UV-B) of UV-B radiation for 7h per day. The plants were grown in pots containing vermiculite and watered with 70% of full strength nitrogen-free Long Ashton solution, containing either low (42.3ppm) or high (282ppm) nitrogen as ammonium nitrate. High nitrogen increased dry matter of stem, leaves and shoot, photosynthetic pigments and photosynthesis (A) without any alteration in stomatal conductance (gs) nor transpiration (E) while it reduced the intercellular CO2 (Ci) concentration, and malondialdehyde (MDA) content. High UV-B radiation had negative effects on dry matter production, A, gs and E with the effects more marked under high nitrogen, whereas it increased Ci under high nitrogen. Activity of PG-POD was reduced by high UV-B radiation under low nitrogen but it was not changed under high nitrogen. The UV-B radiation increased the MDA content independently of nitrogen level. Results indicate that the effects of UV-B radiation on sunflower plants are dependent of nitrogen supply with high nitrogen making their physiological processes more sensitive to UV-B radiation.
The sensitivity of sunflower (Helianthus annuus L.) plants to UV-B radiation is altered by nitrogen status
Keywords: Antioxidants; Growth; Malondialdehyde; Peroxidation; Photosynthesis